Carbon dioxide net assimilation exchange in a young pecan nut orchard during the growth cycle - A. Zermeño-Gonzalez; E.A. Jimenez-Alcala; J.A. Gil-Marin; H. Ramirez-Rodriguez; M. Cadena-Zapata; A.I. Melendres-Alvarez (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Pecan nut trees (Carya illinoensis K), due to their condition as woody and long-living species, in addition to the contribution of nuts for consumption, may also have an essential role in assimilating carbon dioxide and sequestering atmospheric carbon. This study aimed to determine the carbon dioxide net ecosystem exchange of an orchard of young pecan nut trees in northern Mexico, and its relationship with the growth months of the trees.METHODS: The study was carried out from March to November 2017 in a six-year-old pecan nut tree orchard containing trees of the Western Schley and Wichita varieties. The orchard is drip-irrigated with buried tape. The carbon dioxide net ecosystem exchange between the canopy of the orchard trees and the atmosphere was determined with eddy covariance measurements using a three-dimensional sonic anemometer and an open-path infrared carbon dioxide analyzer.FINDINGS: The highest daytime carbon dioxide net ecosystem exchange rate corresponded with the peak absorption rate of photosynthetically active radiation absorbed by the trees' canopy. It was observed between 11:00 and 14:00 hours throughout the growth months of the trees. The highest carbon dioxide net ecosystem exchange rate was observed in June, at 7 micro mol square meter per second. The relationship between the carbon dioxide net ecosystem exchange and the photosynthetically active radiation absorbed by the trees’ canopy through the growth months was described using a rectangular hyperbolic function. From March to September, the carbon sequestration of the young pecan nuts was 0.962 tons of carbon per hectare.CONCLUSION: The highest carbon dioxide diurnal assimilation rate was observed in May, at 5 717.95 millimoles per square meter. Despite the young age of the pecan trees, the orchard has a retention capacity of 0.962 tons of carbon per hectare for the months evaluated. The young pecan orchard significantly contributes to the assimilation and retention of atmospheric carbon that will increase with the growth of the trees, due to greater leaf and biomass development.